Analisis Efektivitas dan Efisiensi Penggunaan Dana Serta Dampak Terhadap Kinerja Keuangan (Studi Kasus Rumah Sakit Stroke Nasional Bukittinggi) - Yulistia Yulistia (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
The purpose of this study: 1) to find out the level of effectiveness and efficiency of working capital 2) To find out financial performance 3) To determine the relationship of working capital effectiveness with financial performance. 4) To find out the relationship between working capital efficiency and financial performance. This study uses the RS Bukittinggi National Stroke as object research, with a population of financial statements observed from 2012 - 2018 and the sample used is the Total Sampling technique. The analytical method used in this study uses the analysis of Ratio, Reward Ratio for Fixed Assets and Correlation Analysis. The results showed : 1. that working capital management at Bukittinggi National Stroke Hospital had not been carried out effectively and efficiently. This can be seen that there has been a decline in financial performance in the past six years. 2. In addition there is a positive and strong relationship between the effectiveness of working capital with financial performance with a correlation interval value of 0.7114 and there is a positive and very strong relationship between working capital efficiency with financial performance with a correlation interval value of 0.871. The working capital at Bukittinggi National Stroke Hospital is used more to make payments for activities with less liquidity